TINJAUAN YURIDIS PIDANA TAMBAHAN PEMECATAN TERHADAP OKNUM TNI YANG MELAKUKAN PENYALAHGUNAAN NARKOTIKA - Nahor, T. Banjar; Ngadiyanto; Yusuf, Ahmad (Collegium Studiosum Journal, 2025)
This study aims to determine the law enforcement mechanism against TNI members involved in narcotics abuse, sentenced to additional punishment of dismissal from military service and the impact of imposing additional punishment of dismissal from military service can reduce the level of narcotics abuse in the TNI environment. This study is a type of normative legal research. The results of the study concluded that law enforcement against TNI soldiers who commit narcotics abuse crimes are sentenced to additional punishment of dismissal based on Article 127 Paragraph (1) letter a of the Republic of Indonesia Law Number 35 of 2009 concerning Narcotics Juncto Article 26 of the Criminal Code Juncto Article 190 Paragraph (1), Paragraph (3) and Paragraph (4) of the Republic of Indonesia Law Number 31 of 1997 concerning Military Justice and other relevant statutory provisions, then the defendant Peltu Mulyawan should be punished and additionally dismissed from military service. The imposition of additional criminal penalties of dismissal can reduce the number of drug abuse in the TNI environment by imposing a principal prison sentence and an additional sentence in the form of dismissal from military service, as has been decided by the Panel of Judges against the Defendant Peltu Mulyawan. If in a settlement of a narcotics crime case committed by a TNI soldier, the judge does not impose an additional criminal sentence of dismissal, then this will actually have the effect of disrupting discipline and greater military interests with the presence of soldiers who commit narcotics crimes on duty, because the negative impacts caused by narcotics in the form of nerve damage and mental health as well as physical decline due to narcotics, will make devotion less than optimal.